2011
DOI: 10.37236/587
|View full text |Cite
|
Sign up to set email alerts
|

Vertex-Transitive $q$-Complementary Uniform Hypergraphs

Abstract: For a positive integer $q$, a $k$-uniform hypergraph $X=(V,E)$ is $q$-complementary if there exists a permutation $\theta$ on $V$ such that the sets $E, E^{\theta}, E^{\theta^2},\ldots, E^{\theta^{q-1}}$ partition the set of $k$-subsets of $V$. The permutation $\theta$ is called a $q$-antimorphism of $X$. The well studied self-complementary uniform hypergraphs are 2-complementary. For an integer $n$ and a prime $p$, let $n_{(p)}=\max\{i:p^i \text{divides} n\}$. In this paper, we prove that a vertex-transitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…In [22] it was shown that Γ Γ is a core whenever Γ is strongly regular and self-complementary (see also the arXiv version [26,Theorem 5.7]). The same conclusion was obtained in [23] (see also [26, Theorem 5.10]) for all vertex-transitive self-complementary graphs Γ, provided that Γ is corecomplete, i.e. Γ is either a core or it has an endomorphism that maps Γ onto a maximum clique.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…In [22] it was shown that Γ Γ is a core whenever Γ is strongly regular and self-complementary (see also the arXiv version [26,Theorem 5.7]). The same conclusion was obtained in [23] (see also [26, Theorem 5.10]) for all vertex-transitive self-complementary graphs Γ, provided that Γ is corecomplete, i.e. Γ is either a core or it has an endomorphism that maps Γ onto a maximum clique.…”
Section: Introductionsupporting
confidence: 73%
“…In [26,Corollary 3.8] it was recently proved that the complementary prism Γ Γ is vertextransitive if and only if Γ is vertex-transitive and self-complementary. In [23] it was proved that a vertex-transitive complementary prism Γ Γ is a core whenever Γ is a core or its core is complete. In Corollaries 4.3 and 4.7 we consider the only vertex-transitive selfcomplementary graphs the author is aware of, which are neither cores nor their cores are complete.…”
Section: Accepted Manuscript 4 Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations